The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 25th International Conference on Compiler Construction 2016
DOI: 10.1145/2892208.2892214
|View full text |Cite
|
Sign up to set email alerts
|

Performance implications of transient loop-carried data dependences in automatically parallelized loops

Abstract: Recent approaches to automatic parallelization have taken advantage of the low-latency on-chip interconnect provided in modern multicore processors, demonstrating significant speedups, even for complex workloads. Although these techniques can already extract significant thread-level parallelism from application loops, we are interested in quantifying and exploiting any additional performance that remains on the table. This paper confirms the existence of significant extra threadlevel parallelism within loops p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Instead, all SCCs are treated equal and merged in the graph to coarsen the granularity of potential parallel regions by applying typed fusion. HELIX [8,30] is a speculatively parallelizing compiler, which would benefit from iterator recognition. While HE-LIX applies parallelizing loop transformations, it relies on normalizable loops (equivalent to while loops), but it does not attempt to separate loop iterator code.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, all SCCs are treated equal and merged in the graph to coarsen the granularity of potential parallel regions by applying typed fusion. HELIX [8,30] is a speculatively parallelizing compiler, which would benefit from iterator recognition. While HE-LIX applies parallelizing loop transformations, it relies on normalizable loops (equivalent to while loops), but it does not attempt to separate loop iterator code.…”
Section: Discussionmentioning
confidence: 99%
“…HELIX parallelizes a loop by distributing its iterations between cores [23,24,42]. Each iteration is sliced into several sequential and parallel segments.…”
Section: Transformations Built Upon Noellementioning
confidence: 99%
“…On the other hand, recent work has shown that dependence analysis, even when informed with perfect profiling information, is inherently unable to identify any further latent parallelism [25].…”
Section: Introductionmentioning
confidence: 99%